Structure, morphogenesis of calyptra and nomenclatural identity of Trichodesmium erythraeum Ehr. (Cyanobacteria) newly recorded off the Southwest coast of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2020)
Trichodesmium erythraeum Ehrenberg 1830 (Cyanobacteria) has been described and newly recorded from three km off the west coast of the St. Martin’s Island (SMI), Cox’s Bazar, Bangladesh. The Red Sea algal bloom was narrowly elliptical raft-like loose aggregates 20-40 cm long, 4-8 cm wide and 2-3 cm thick. Volume of small and large Sea sawdust were 160×10-6 to 960×10-6 m3 consisting of 25-153 millions flat tuft or spindlelike colonies measured 830-1500 μm long and 155-260 μm wide with 13-16 filaments laterally in the median region. Sheath was present around each trichome even covering the tip cell wall the feature has so far not been reported for the Trichodesmium spp. Because of most likely sticky nature of the sheath 300-600 μm long filaments of 195-450 formed compact colonies without colonial sheath around. In interior filaments cells were rectangular 7-10 μm long and 6.3-10 μm wide with abundant gas vacuoles, bluish-green red, no diazocytes developed and without calyptrae. Cells of peripheral filaments were without gas vacuoles, cytoplasm disorganized, appearing necrotic with glycogen granules, and produced convex to sickle-shaped four-layered calyptra consisting of outermost sheath followed by outer extra thick wall, tip cell wall and inner extra thick wall on the tip cell. Calyptra was also produced on tip cells of tapered filaments. Presence of sheath around each trichome binding all filaments into a colony without colonial sheath described here, and presence of nitrogenase containing diazocytes in interior filaments, both temporal and spatial segregation of N2 fixation and photosynthesis within the photoperiod described and discussed in literature made the authors to consider T. erythraeum Ehr. a distinct taxon under family Microcoleacece.Bangladesh J. Plant Taxon. 27(2): 273-282, 2020 (December)